Tumour necrosis factor production and natural killer cell activity in peripheral blood during treatment with recombinant tumour necrosis factor. - Männel, D. N. (Nature Publishing Group, 1989)
Tumour necrosis factor (TNF) has been found to be an important immunomodulator. Among other functions TNF activates natural killer (NK) cells and stimulates monocytes/macrophages in an autocrine fashion. TNF production and NK activity in peripheral blood mononuclear cells were determined in a clinical phase I study in which recombinant human (rh) TNF was administered as a continuous infusion weekly for a period of 8 weeks. Even though TNF production and NK activity were significantly reduced directly after rhTNF infusion the effect proved to be transient and most pronounced at the first rhTNF administration. One day after completion of the rhTNF infusion the peripheral cells released more TNF into the supernatant compared to TNF activity immediately before the rhTNF infusion. This effect was conspicuous in non-stimulated cultures. After repeated rhTNF infusions both stimulated and non-stimulated TNF production of the peripheral blood mononuclear cells was increased. NK cell activity was also enhanced after repeated cycles of rhTNF administration as compared to early rhTNF treatment. Thus, repeated rhTNF infusions lead to a stimulatory effect on TNF production and NK activity of peripheral blood cells.